The New Encyclopaedia Britannica: Propaedia: Outline of Knowledge: Volume 30: Guide to The Britannica (Chicago Encyclopaedia Britannica Inc., 1994)
32 v. : ill. (some col.), maps ; 29 cm. + Supplement.
v. 1-12. Micropaedia -- v. 13-29. Macropaedia -- [v. 30] Propaedia -- [v. 31-32] Index -- Supplement 1-2. Encyclopaedia Britannica Inc. Peter B. Norton, President and Chief Executive Officer Joseph J. Esposito, President, Publishing Group Chicago Auckland/London/Madrid/Manila/Paris/Rome/Seoul/Sydney/Tokyo/Toronto
Spine Title: Britannica. . in 32 Volumes . Special Edition: The Anniversary Edition Is Limited to 49,999 Sets Numbered from 1 to 49,999. This Is Set Number 36933
Keywords: Encyclopedias (3GdehShYGJs; General; Encyclopedias and dictionaries